Empowering Pregnant Women with Health Promotion Strategies to Prevent Chronic Energy Deficiency (CED): Systematic Review - Ratna Indriyani; Yenny Puspitasari; Novita Ana Anggraini (Journal of Nursing Practice)
Background: Pregnant women's nutrition is very important for the growth and development of the fetus. Nutrition for pregnant women is very important for the development and growth of the fetus. The application of the concept of a health promotion model strategy as the right strategy to improve and prevent CED is urgently needed.